Case Report: Scurvy—a modifiable cause of psychiatric refractoriness and lithium pharmacokinetic abnormalities in autism - Geiser, Marie; Guggisberg, Nicolas; Convertini, Josephine; Crettol, Severine; Ansermot, Nicolas; Guinchat, Vincent (Frontiers in Psychiatry, 2026)
Scurvy, although rare in developed countries, can notably occur in individuals with extreme dietary selectivity, particularly those with neurodevelopmental disorders. We describe the case of an 18-year-old woman with autism spectrum disorder and severe intellectual disability who presented with severe behavioral dysregulation and limited response to multiple psychotropic regimens. Despite progressive lithium dose escalation, serum levels remained subtherapeutic. The turning point came with the diagnosis of profound vitamin C deficiency (ascorbic acid <1 µmol/L), prompting high-dose supplementation. Within days, the patient showed rapid behavioral improvement and a marked rise in serum lithium concentrations, necessitating dose reduction. First, nutritional deficiencies—particularly scurvy—can manifest primarily through psychiatric and behavioral symptoms in vulnerable populations, often resulting in misdiagnosis and polypharmacy. Second, although still speculative, we hypothesize that vitamin C status may affect lithium pharmacokinetics. This case underscores the importance of nutritional screening in refractory psychiatric presentations, particularly in individuals with restrictive diets, and highlights a potentially underrecognized interaction between vitamin C and lithium that warrants further investigation.